Decreased Serum Oxytocin and Increased Homocysteine in First-Episode Schizophrenia Patients - Liu, Yong; Tao, Huai; Yang, Xiudeng; Huang, Kai; Zhang, Xianghui; Li, Cunyan (Frontiers in Psychiatry, 2019)
Schizophrenia (SZ) is a debilitating and heterogeneous disease. We hypothesized that oxytocin (OXT) system, inflammation and one-carbon metabolism would have a link with SZ. In this study, serum OXT, OXT receptor (OXTR), interleukin-6 (IL-6), high sensitivity CRP (hsCRP) and homocysteine (Hcy) levels were measured in fifty-two first-episode schizophrenia (FES) patients and forty-one healthy controls (HC) from the Second Xiangya Hospital of Central South University. Meanwhile, the mRNA expressions of OXT and OXTR genes were determined by real-time quantitative PCR. Serum OXT and OXTR levels were significantly lower in FES patients (518.96 ± 22.22 and 174.60±17.11 pg/ml) than HC group (711.58 ± 40.57 and 252.15 ± 20.62 pg/ml). Serum IL-6 and hsCRP levels showed no difference between two groups (1.82 ± 0.30 vs 1.69 ± 0.36 pg/ml, 0.66 (0.22, 1.07) vs 0.31 (0.13, 0.91) mg/L), but serum Hcy levels were significantly higher in FES patients (20.18 ± 1.83 vs 15.24 ± 0.82 μmol/ml). The FES patients (0.27 ± 0.02 and 0.20 ± 0.02) have relatively higher mRNA expressions of OXT and OXTR genes than HC group (0.16 ± 0.01 and 0.14 ± 0.01). In summary, our results suggested the possible function of OXT system and Hcy in the pathogenesis of SZ.